Chromate reduction by PVA-alginate immobilized streptomyces griseus in a bioreactor - Poopal, Ashwini C.; Laxman, Ryali Seeta (Biotechnology Letters, 2009)
Microbial reduction of toxic Cr(6+) to the less toxic Cr(3+) is potentially a useful bioremediation process. Among the matrices tested for whole cell immobilization of an efficient chromate-reducing Streptomyces griseus strain, PVA-alginate was the most effective and was used for reduction of Cr(VI) in a bioreactor. Cr(6+) reduction efficiency decreased as Cr(6+) was increased from 2 to 12 mg l(-1) but increased with an increase in biomass concentration. However, increasing the flow rate from 2 to 8 ml h(-1) did not significantly affect Cr(6+) reduction. The reduction was faster in simulated effluent than in synthetic medium and complete removal of 8 mg Cr(6+) l(-1) from effluent and synthetic medium occurred in 2 and 12 h, respectively. Our results indicate that immobilized S. griseus cells could be applied for the large-scale bioremediation of chromate-containing effluents and wastewaters.
Keywords: Bioremediation; Chromate reduction; Immobilized cells; Polyvinyl alcohol-alginate; Streptomyces griseus